Competition between Li+ and Na+ in sodium transporters and receptors: Which Na+-Binding sites are "therapeutic" Li+ targets?. Issue 17 (9th April 2018) - Dudev, Todor; Mazmanian, Karine; Lim, Carmay
Abstract : Li + (turquoise), the better charge acceptor, can displace Na + (purple) bound by only one or two aa residues in buried sites. Thus, Li + can displace Na + bound by Asp − and Ser in the A2A AR/β1 AR receptor and enhance the metal site's stability, thus prohibiting structural distortions induced by agonist binding, leading to lower cytosolic levels of activated G-proteins, which are hyperactive in bipolar disorder patients. Abstract : Sodium (Na + ) acts as an indispensable allosteric regulator of the activities of biologically important neurotransmitter transporters and G-protein coupled receptors (GPCRs), which comprise well-known drug targets for psychiatric disorders and addictive behavior. How selective these allosteric Na + -binding sites are for the cognate cation over abiogenic Li +, a first-line drug to treat bipolar disorder, is unclear. Here, we reveal how properties of the host protein and its binding cavity affect the outcome of the competition between Li + and Na + for allosteric binding sites in sodium transporters and receptors. We show that rigid Na + -sites that are crowded with multiple protein ligands are well-protected against Li + attack, but their flexible counterparts or buried Na + -sites containing only one or two protein ligands are vulnerable to Li + substitution. These findings suggest a novel possible mode of Li + therapeutic action: By displacing Na + bound by ≤2 protein ligands in buried GPCR sites and stabilizing the receptor's inactive state, Li + could prohibit conformational changes to an active state, leading to lower cytosolic levels of activated guanine nucleotide-binding proteins, which are hyperactive/overexpressed in bipolar disorder patients.